1997
DOI: 10.1097/00001756-199712220-00026
|View full text |Cite
|
Sign up to set email alerts
|

Activity in the parietal area during visuomotor learning with optical rotation

Abstract: Regional cerebral blood flow (rCBF) was measured in six subjects to study changes of activity in the parietal cortex during learning of a visually guided pointing task with a discrepancy of visuomotor coordination and to determine whether reorganization affects the parietal activity after learning. During the early stage of learning, the right posterior parietal cortex showed a significant increase in rCBF. During the late stage, on the other hand, significant activation was noted in the postcentral gyrus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 9 publications
5
40
2
Order By: Relevance
“…Finally, we obtained activation in the right posterior parietal cortex, as previously shown (Ghilardi et al 2000;Inoue et al 1997Inoue et al , 2000. Interestingly, of the 3 regions activated during the ROT task only the posterior parietal cortex showed a linear increase in activation from CONTROL to ROTalt to ROT.…”
Section: Learning a Rotated Reference Framesupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, we obtained activation in the right posterior parietal cortex, as previously shown (Ghilardi et al 2000;Inoue et al 1997Inoue et al , 2000. Interestingly, of the 3 regions activated during the ROT task only the posterior parietal cortex showed a linear increase in activation from CONTROL to ROTalt to ROT.…”
Section: Learning a Rotated Reference Framesupporting
confidence: 82%
“…Similarly, the presence of 2 phases of learning suggests differences in the fast and slow processing of directional and extent errors that might be paralleled by differences in brain activation over time. This possibility is supported by imaging studies that have shown modulation and shift in brain regions activated during the time course of motor learning (Inoue et al 1997;Sakai et al 1998). Such shifts have been proposed to reflect the transitions from learning simple stimulus-response associations to learning of sequences (Sakai et al 1999), from novelty to automaticity (Doyon et al 1996;Krebs et al 1998;Petersen et al 1998) or from working memory to consolidation (Shadmehr and Holcomb 1997).…”
Section: Introductionmentioning
confidence: 85%
“…Reduction in overall performance error was associated with reduced activity in the left parietal cortex and the right dentate nucleus. This finding is not unexpected considering other imaging studies that similarly showed parietal and cerebellar regions to be modulated over the course of adaptation (Clower et al 1996;Imamizu et al 2000;Inoue et al 1997Inoue et al , 2000Miall and Jenkinson 2005;Nezafat et al 2001). In particular, Nezafat et al (2001) noted an initial reduction in rCBF to the dentate over the course of the first two scan sessions as subjects adapted to a novel torque perturbation.…”
Section: Performance and Brain Activitysupporting
confidence: 74%
“…To our knowledge, no study has reported abnormalities in somatosensory function in females with Turner syndrome. However, previous studies have suggested that the postcentral gyrus is involved in other capacities, in addition to somatosensory function, including visuomotor learning and spatial working memory (Inoue et al 1997, Thomas et al 1999, Frutiger et al 2000. Furthermore, decreasing tissue volume was significantly correlated with lower IQ scores in the Turner syndrome group, suggesting that tissue loss in this area is associated with deficits in cognitive function.…”
Section: Discussionmentioning
confidence: 86%